Autoamputation of Dermatofibrosarcoma Protuberans: A Novel and Rare Presentation of a Familiar Entity. (August 2019) - Jebastin Thangaiah, Judith; Williamson, Sean R.; Pimentel, Jason; Perry, Kyle
Dermatofibrosarcoma protuberans (DFSP) is categorized as a fibrohistiocytic tumor of intermediate malignant potential. It has significant risk for local recurrence and, less commonly, local or distant metastasis. Initially, these tumors typically arise as a firm plaque on the skin that slowly progresses to a nodular and protuberant dermal lesion. DFSP can also exhibit ulceration, hemorrhage, and accelerated growth, but autoamputation has not been described in the English literature. In this article, we report a case of an asymptomatic classical DFSP on the upper back in which the protuberant portion spontaneously autoamputated. In this case, the residual lesion was treated with Mohs micrographic surgery. The presentation, features, and implications of this interesting mode of presentation are discussed.